2008
DOI: 10.1016/j.bbmt.2008.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Cervical Dysplasia in Long-Term Survivors of Allogeneic Stem Cell Transplantation—Implications for Screening and HPV Vaccination

Abstract: As more women survive allogeneic stem cell transplantation (SCT), the development of genital human papilloma virus (HPV)-related squamous intraepithelial lesions (SIL) warrants study. Thirty-five of 38 females followed prospectively long-term after SCT for hematological malignancies (median: 7 years posttransplant) were adults and had cervical cytology testing. Acute graft-versus-host-disease (aGVHD) occurred in 9 and chronic (cGVHD) in 34 patients. Six (17%) continued receiving systemic immunosuppressive ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 22 publications
4
83
0
5
Order By: Relevance
“…Previous studies found that chronic GvHD was a major factor associated with risk of secondary solid cancer. [19][20][21][22] Although the absence of significant GvHD may not be a long-term goal, particularly for patients with high-risk disease, the relationship among graft sources remained similar even in the weighted analyses. These results favor the use of bone marrow graft for sibling HCT to promote ideal recovery of patients without significant morbidity in the Japanese population.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies found that chronic GvHD was a major factor associated with risk of secondary solid cancer. [19][20][21][22] Although the absence of significant GvHD may not be a long-term goal, particularly for patients with high-risk disease, the relationship among graft sources remained similar even in the weighted analyses. These results favor the use of bone marrow graft for sibling HCT to promote ideal recovery of patients without significant morbidity in the Japanese population.…”
Section: Discussionmentioning
confidence: 95%
“…24,41 Prolonged use of immunosuppressive drugs to treat cGVHD and severity of cGVHD are major risk factors for the development of human papillomavirus (HPV)-related dysplasia 15 and squamous cell carcinoma of the female genital tract. 42 We recommend performing regular gynecological examination including cervical cytology once a year 15,16 (BIIa). In the case of suspicious genital lesions, colposcopy and biopsy are recommended (BIIa).…”
Section: Secondary Malignancies Of the Female Genital Tract After Hsctmentioning
confidence: 99%
“…If the treatment is not successful in a timely manner (6-8 weeks), we perform a biopsy of the lesions to exclude malignancies 15 (AIIa). around the periclitoral hood accompanied by the typical porcelain-white lesions that are easily distinguishable from genital cGVHD.…”
Section: Histopathology and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…einem Drittel der Langzeit-Überlebenden auftritt. Ebenso stellt eine länger andauernde immunsuppressive Therapie aufgrund einer chronischen GvHD ein erhöhtes Risiko für die Entwicklung HPV-induzierter squamöser intraepithelialer Läsionen dar [76,77]. Die Impfung kann jedoch für diese Patienten in Erwägung gezogen werden und ein regelmäßiges HPV-Screening S362 Impfungen bei Immundefekten/Immunsuppression -Expertenstatement und Empfehlungen K consensus report wird speziell empfohlen (Kostenübernahme durch Sozialversicherungsträger zur Zeit nicht geklärt).…”
Section: Hpvunclassified